ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN TERHADAP PENGELOLAAN LIMBAH SEBAGAI SALAH SATU BENTUK PERTANGGUNGJAWABAN SOSIAL (Studi Kasus Pabrik Singkong Di Dusun VI Kelurahan Sidodadi Kecamatan Pekalongan Kabupaten Lampung Timur) - Agnes Nova Liana; Nedi Hendri; Elmira Febri Darmayanti (Jurnal Akuntansi AKTIVA, 2021)
This study aims to determine whether the cassava factory in Hamlet VI, Sidodadi Village, Pekalongan District, East Lampung Regency has implemented an environmental accounting system as a social responsibility to the community, especially in waste and environmental management. The research design used in this study is a qualitative research. The data analysis technique used in this research is comparative descriptive. The results of this study stated that the cassava parch of Dusun VI, Sidodadi Sub-district, Pekalongan District, East Lampung Regency was in accordance with PSAK Paragraphs 82 and 94, correctly acknowledged the postal costs of waste treatment and the measurement of waste processing costs was in accordance with PSAK Paragraphs 99 and 101. In presenting costs waste treatment is in accordance with PSAK Number 1 Paragraph 10, clearly presenting the cost of waste treatment in production costs presented in the factory profit and loss statement. The cassava factory has disclosed accounting policies related to waste treatment costs in the factory's statement of financial position.